Marry me, Millie - Lillard, Amy (Lillard, Amy. Paradise Valley series, 2022)
When her young husband died unexpectedly, Millie Bauman thought her life was over too--until she learned she was carrying his child. Now, as she awaits the baby's arrival, Millie's sure her future will revolve around motherhood, the B&B she runs with her Aunt Sylvie, and the beloved Whoopie Pies her Widows Club whips up each week. But when a handsome newcomer arrives in town, Millie is intrigued, and the club wonders if Millie might find a second chance at love ...